2020
DOI: 10.3906/sag-2006-60
|View full text |Cite
|
Sign up to set email alerts
|

Association between monocyte to high-density lipoprotein cholesterol ratio and bicuspid aortic valve degeneration

Abstract: Background/aim: From a pathophysiological point of view, inflammation is thought to be more dominant in bicuspid aortic valve (BAV) stenosis than tricuspid aortic valve (TAV) stenosis. Our study aimed to determine the association between monocyte to highdensity lipoprotein cholesterol (HDL-C) ratio (MHR), a new inflammatory marker, and the speed of progression of stenosis and pathophysiology of BAV stenosis. Materials and methods: A total of 210 severe aortic stenosis patients (70 consecutive BAV patients, 140… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Moreover, MHR is found to be an independent predictor of long term mortality among myocardial infarction patients 27 . Recently, an association between MHR and bicuspid aortic valve degeneration has also been reported 28 . To date, however, there has been no published clinical study including patients with AD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, MHR is found to be an independent predictor of long term mortality among myocardial infarction patients 27 . Recently, an association between MHR and bicuspid aortic valve degeneration has also been reported 28 . To date, however, there has been no published clinical study including patients with AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…27 Recently, an association between MHR and bicuspid aortic valve degeneration has also been reported. 28 To date, however, there has been no published clinical study including patients with AD patients. The present study, for the first time, reveals the clinical significance of MHR in predicting intrahospital mortality in patients with AD.…”
Section: Discussionmentioning
confidence: 99%
“…6 This study is the first in the literature to investigate the prognostic relationship between MHR and TAAD, yet, MHR has been linked with myocardial infarction as well as bicuspid aortic valve degeneration, proving to be a useful tool in tackling the cardiovascular disease. [6][7][8] Xie et al 9 studied and confirmed MHR as a biomarker for in-hospital and long-term mortality in patients undergoing endovascular repair for acute type b AD. Additionally, Du et al 10 looked at the diagnostic value of MHR in acute AD, providing further evidence in its favor.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MHR reflects both immune and metabolic status and is associated with pathological processes in many diseases (30)(31)(32)(33)(34). In patients with atherosclerotic CV disease mainly characterized by inflammation and lipid deposition, MHR has a significant prognostic role.…”
Section: Discussionmentioning
confidence: 99%